AI for Business (O'Reilly Media, Inc., 2016)
AI is taking off, but traveling into uncharted territory. Where is AI going and what does it mean for business? In this O'Reilly video collection, four AI experts discuss the business-side of AI. They discuss how companies can get started building AI products, what product development should (and shouldn't) look like, how organizations can successfully and thoughtfully use AI advancements to improve efficiency and production, and what we can expect from the future of AI. Each video segment in this collection comes from the 2016 O'Reilly Artificial Intelligence Conference.